Estudo taxonômico de Maruina Müller, 1895 (Diptera: Psychodidae) do Brasil - Camico, Jéssica Luna (Instituto Nacional de Pesquisas da Amazônia - INPA, 2017)
Maruina Müller, 1895 is currently the only genus of the tribe of Maruinini, with 37 species described, being nine known species in Brazil. The objective of this study was to perform a taxonomic study of Brazilian species of Maruina, and provide an identification key to these species. Holotypes and paratypes of six described were analyzed, from the Museum of Zoology of the University of São Paulo (MZUSP) and professor Johann Becker Entomological Collection of Zoology Museum of Feira de Santana State University (MZFS). Material from field trips made by other researchers of National Institute of Amazonian Research (INPA) where mounted in permanent slides according to Bravo (1996). Five new species are described, and new records of two other species are presented. It is also the first record of the genus in the Brazilian Amazon, since in Brazil, were only known species for the Atlantic forest. The diagnosis of the subgenera was updated and it is described the first species of Maruina with thirteen flagellomeres. For each subgenus is provided an identification key to males and females and a map with species distributions.
Keywords: Maruina; Diptera; Insetos